Countries' Structural Characteristics and the Magnitude of Fiscal Shock - Senekovič, Marko (Naše gospodarstvo/Our economy, 2025)
The transmission channels of stabilizing fiscal policy remain partially unexplored, which presents a challenge for the effective management of economic policy. Using a broad dataset and vector autoregression methodology, this paper examines the relationship between selected structural characteristics of economies and the magnitude of fiscal multipliers. The results indicate that fiscal multipliers tend to be smaller in more developed economies, in business-friendly environments, and in EU and EMU member states. Additionally, findings on public and private debt, as well as savings levels, suggest that fiscal multipliers are higher in countries where a larger share of economic agents faces liquidity constraints. Consequently, increased public spending, driven by households' higher marginal propensity to consume, produces a stronger impact on output through the multiplier effect. Our results provide a foundation for fiscal policymakers to design appropriate measures tailored to the specific characteristics of individual economies, aiming to enhance the effectiveness of stabilization policies. Consequently, fiscal stimulus can achieve a greater impact while ensuring the efficient allocation of taxpayer resources.